Capital Structure in the Context of Taxation and Financial Access: A Theoretical Synthesis - Mujiyati, Mujiyati; Imronuddin, Imronuddin; Setyawan, Anton Agus (International Journal of Management Science and Information Technology, 2026)
This study examines the evolution and integration of capital structure theories and their implications for firm value, with emphasis on taxation and financial access in emerging markets. It applies a systematic literature review supported by bibliometric analysis and narrative synthesis. The article selection process followed PRISMA guidelines, covering identification, screening, eligibility assessment, and final inclusion. Articles were collected from Scopus and ScienceDirect using keywords related to capital structure, taxation, tax shield, financial access, financing constraints, firm value, and emerging markets. The final corpus was analyzed through keyword co-occurrence, thematic mapping, thematic evolution, co-citation analysis, bibliographic coupling, and qualitative narrative synthesis. The findings show that capital structure research has shifted from a static optimality perspective toward a more contextual and institutionally grounded framework. Although debt financing may enhance firm value through tax shields, these benefits are often constrained by information asymmetry, limited external finance, and institutional pressures. The results indicate that taxation and financial access should not be treated as separate determinants, but as interrelated mechanisms shaping corporate financing decisions. The study contributes by developing an integrative theoretical synthesis linking classical capital structure theories with taxation, financial access, agency conflicts, and institutional context in emerging markets, particularly Indonesia.